PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA KELAS XISMK AL-HIDAYAH WULUHAN JEMBER - Imam Bukhori Muslim (Pendidikan Biologi,Universitas Islam Jember, 2016)
Education system in Indonesia has experienced much change. This change is happen because of wish to be better. First observation in the XI class at SMK Al-Hidayah Wuluhan proves low students participation in teacher questions, low student activity in study club and class presentation. Learning activity is dominated by teacher, so students more passive in learning activity. Observation proves learning outcome of IPA cognitive which is low because 30 percent students hasn’t fulfill KKM (70). Low student involvement in learning activity is believed impact to low learning outcome of students cognitive. This research has aim to find out the effectiveness guided inquiry learning model application in increase of learning outcome of students cognitive. This type of research is the Classroom Action Research. This research was held from 20 October to 20 November 2016 with the subject of much research as 14 students. Result of research observation shows learning activity well and effectively. Learning outcome of students cognitive with good criteria is ? 80% studentshave completed. Learningoutcome of students cognitive in first cycle is 68,57. Whereas, learning outcome of students cognitive in second cycle is 72,5. So, learning outcome of students cognitive increases 3,93 point. Conclusion from this research result is guided inquiry learning model application effective in increase learning outcome of students cognitive.Keywords: Guided Inquiry, learning outcome of students cognitive.